Exploring commitment among union members: Perspective and direction - Johari, Husna; Ghazali, Sabarani (World Business Institute, 2011)
Basically, unions offer the promise of a number of benefits in order to solicit members’ commitment. Unions are traditionally different from commercial organizations in various aspects such as historical development, the voluntary nature of their membership and the sources of power.In this context, unions involve with the lack of formal authority over members and the need for members’ voluntary participation. The union’s lack of formal authority over its members is due to the differences in the nature of exchange between the workers, the union and the working organization. This difference in dynamics means that the union must convince union members of its usefulness and also emphasize the importance of members’ commitment to increase the union’s effectiveness. Consequently this demands separate scrutiny from that of commercial organization. The study of unions as organizations requires an awareness of the unique functions of these organizations and their nature of member attachment to their union.The dramatic changes in the surrounding environment have contributed a serious impact on the performance and effectiveness of unions. In order to regain support for unions, it is necessary and important to understand what determines union commitment. Consequently, this study focused on trade unions to identify some of the salient factors that may influence the commitment of union members from different sectors in Malaysia. This study also examined the influence of the union sector as a moderator on the relationship between the factors and union commitment. Based on the research findings, theoretical and practical implications are discussed further.